An Approach to Assessing the National Multidimensional Poverty Line in Russia - Kormishkina, Ludmila; Kormishkin, Evgenii; Ermakova, Eka; Koloskov, Dmitrii (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
This study aims to econometrically assess multidimensional poverty in Russia with regard to the quantitative and qualitative parameters of the population’s life-sustaining activities. Russia’s partial integrated poverty indices were constructed based on a combination of quantitative and qualitative parameters characterizing the possibilities of satisfying needs in the main spheres/sectors of human values. The indicators that affect the poverty level in the country were determined using linear regression models. The available time lag in the regression models enabled us to make a short-term forecast of changes in the poverty level in Russia. The proposed approach to assessing the national poverty level considers monetary indicators related to the level of income of the population, the affordability of services necessary to meet human needs, and the presence of opportunity costs, which imply sacrificing a person’s free time to ensure the material wellbeing necessary for life